The effect of adopting pediatric protocols in adolescents and young adults with acute lymphoblastic leukemia in pediatric vs adult centers: An IMPACT Cohort study. (26th March 2019) - Gupta, Sumit; Pole, Jason D.; Baxter, Nancy N.; Sutradhar, Rinku; Lau, Cindy; Nagamuthu, Chenthila; Nathan, Paul C.
Abstract: Background: Retrospective studies have shown adolescents and young adults (AYA) with acute lymphoblastic leukemia (ALL) have superior survival when treated in pediatric versus adult centers (locus of care; LOC). Several adult centers recently adopted pediatric protocols. Whether this has narrowed LOC disparities in real–world settings is unknown. Methods: The IMPACT Cohort is an Ontario population–based cohort that captured demographic, disease and treatment (treatment protocol, chemotherapy doses) data for all 15‐21 year olds diagnosed with ALL 1992‐2011. Cancer outcomes were determined by chart abstraction and linkage to provincial healthcare databases. Treatment protocols were classified as pediatric‐ or adult‐based. We examined predictors of outcome, including LOC, protocol, disease biology, and time period. Results: Of 271 patients, 152 (56%) received therapy at adult centers. 5‐year event‐free survival (EFS ± SE) among AYA at pediatric vs adult centers was 72% ± 4% vs 56% ± 4% ( P = 0.03); 5‐year overall survival (OS) was 82% ± 4% vs 64% ± 4% ( P < 0.001). After adjustment, OS remained inferior at adult centers (hazard ratio 2.5; 95% confidence interval 1.1‐6.1; P = 0.04). In the most recent period (2006‐2011), 39/59 (66%) AYA treated at adult centers received pediatric protocols. These AYA had outcomes superior to the 20 AYA treated on adult protocols, but inferior to the 44 AYA treated at pediatric centers (EFS 72% ± 5% vs 60% ± 9% vs 81% ± 6%; P = 0.02; OS 77% ± 7% vs 65% ± 11% vs 91% ± 4%; P = 0.004). Induction deaths and treatment–related mortality did not vary by LOC. Conclusions: Survival disparities between AYA with ALL treated in pediatric vs adult centers have persisted over time, partially attributable to incomplete adoption of pediatric protocols by adult centers. Although pediatric protocol use has improved survival, residual disparities remain, perhaps due to other differences in care between adult and pediatric centers. Abstract : Previous studies demonstrated that pediatric–based acute lymphoblastic leukemia (ALL) protocols were associated with superior adolescent and young adult (AYA) outcomes than cohorts treated with adult–based protocols. Using a population–based AYA database, we found that though pediatric–based protocols were adopted for many AYA in adult centers and that these patients experienced superior outcomes to AYA treated with adult–based protocols, their outcomes were still inferior to AYA treated at pediatric institutions.